BIOTYPICAL VARIABILITY AMONG FOUR POPULATIONS OF RED PALM WEEVIL RHYNCHOPHORUS FERRUGIAEUS FAB/OLIV. FROM DIFFERENT PARTS OF INDIA - C.P. Ramachandran (International Coconut Community Journal, 1998)
The red palm weevil rhpichophorus ferrugineus FAB/OLIV is a very serious and dreaded pest of coconut, date and other palms. Being an internal feeder the weevil incidence is detected at a very late stage when the tree has succumbed to weevil attack. Hence conventional control operations may not be very effective. The biotypical variability of the four populations collected from different parts of India showed that the populations are genetically different and strainal variability exists between them. Variations in sex ratio and deleterious genetic effect were observed in the crosses and reciprocal crosses. The weevil has a very high fitness due to high production potential and the absence of effective parasites, predators and pathogens. In spite of the high fitness, in endemic areas weevil population tend to remain at certain levels of intensity. This may be due to certain limiting factors.